SİVİL HAVACILIK GÜVENLİĞİNDE EĞİTİM STANDARDİZASYONU. - ERGÜN, Nalan (Journal of International Social Research / Uluslararası Sosyal Araştırmalar Dergisi, 2014)
The primary aim of this study is to analyze the standardization of the training via the national and international regulations for aviation security personnel who play a significant role in the implementation of aviation security services. In line with this purpose, first of all, the study emphasizes the key importance of security personnel. The differences between the concepts of certificate and license that are used to provide standardization of training for the personnel working in different departments in aviation sector are researched by discussing the related documents. As a result, taking into consideration the international structure of security services, it is suggested that standardization of training for aviation security personnel should be done through licensing.